MEMPERKUAT KEARIFAN LOKAL UNTUK MENANGKAL INTOLERANSI UMAT BERAGAMA DI INDONESIA - Laurensius Arliman S (Scopus ID: 57202307632) (Ensiklopedia of Journal, 2018)
The issue of religious intolerance is a problem that is always warm in the life of society, nation and state. Until now, there are still many community groups that carry out intolerance. Just look at the case of rejection of the construction of the church in the majority area of its people is Muslim, and vice versa against the refusal of the construction of mosques in areas where the majority are non-Muslims. On this matter, this paper wants to examine the strengthening of local wisdom to counteract religious intolerance in Indonesia, using normative legal research methods. To carry out local wisdom, there are many social institutions that live in the midst of society, one of which is traditional leaders or traditional elders in the local area. The role of traditional leaders or traditional elders is very important in solving problems that arise in people's lives. One of them is intolerance of religious people.